Trừ cả 2 vế cho 7 ta được:
\(\frac{x^2+2006x-1}{2006}-1+\frac{x^2+2006x-2}{2005}-1+...+\frac{x^2+2006x-7}{2000}-1\)
\(=\frac{x^2+2006x-8}{1999}-1+...+\frac{x^2+2006x-14}{1993}-1\)
=> \(\frac{x^2+2006x-2007}{2006}+\frac{x^2+2006x-2007}{2005}+...+\frac{x^2+2006x-2007}{2000}=\frac{x^2+2006x-2007}{1999}+...+\frac{x^2+2006x-2007}{1993}\)
=> \(\left(x^2+2006x-2007\right)\left(\frac{1}{2006}+\frac{1}{2005}+...+\frac{1}{2000}-\frac{1}{1999}-...-\frac{1}{1993}\right)=0\)
=> x2 + 2006x -2007 = 0. Vì \(\frac{1}{2006}+\frac{1}{2005}+...+\frac{1}{2000}
mình sửa lại chút sai xót bài giải trên: nhận xét 1/2006+...+ 1/2000-1/1999-...- 1/993 < 0 nhé! sửa dấu + thành dấu -